Penggunaan Setsuzokushi Tonikaku, Tokorode, dan Jyaa dalam Novel Norwei No Mori Karya Haruki Murakami - Kusumasari, Ni Made Intan; Anggraeny, Renny; Luhur Wedayanti, Ni Putu (Humanis, 2019)
The title of this thesis is "Use of Setsuzokushi Tonikaku, Tokorode, and Jyaa found in the Novel Norwei No Mori by Haruki Murakami.” focuses on studying the structure and meaning of Setsuzokushi Tonikaku, Tokorode, and Jyaa. The theories which use are Sunagawa et al (1998), Makino and Tsutsui (1994), and semantic theory according to Pateda (2001), and syntactic theory according to Verhaar (2012). This research was analyzed by using agih method and divide technique, the presentation about results of analysis used informal method. The results of this analysis are Setsuzokushi tonikaku, tokorode, jyaa connected with the first sentence and the second sentence, connected with Godan Doushi, Ichidan Doushi, Henkaku Doushi, Meishi, and Keiyoushi. The most found structure are Godan Doushi and Meishi, while in terms of its meaning the most found is the context of the situation for change the topic of conversation.